Математическое моделирование электромагнитных характеристик электротехнических сталей - Пуйло, Глеб Васильевич; Насыпаная, Елена Петровна; Левин, Дмитрий Михайлович (НТУ "ХПИ", 2011)
Обоснована необходимость математического моделирования и автоматизированного формирования аналитических моделей электромагнитных характеристик электротехнических сталей для исследовательского проектирования, синтеза, анализа и оптимизации электротехнических устройств. Сформулированы требования к этим математическим моделям и предложен алгоритм их автоматизированного формирования.

The necessity of mathematical simulation and computer-assisted forming of analytical models for electric steels electromagnetic characteristics with the purpose of research designing, synthesis, analysis and optimization of electrical devices is grounded. Requirements for these mathematical models are formulated, an algorithm of their computer-assisted forming on the basis of flat approximating functions with an exponential kernel developed, which allows obtaining mathematical models in the form of repeatedly differentiable functions that satisfy specified requirements for the approximation accuracy.
Mathematical simulation of electromagnetic characteristics of electric steels
Keywords: преобразователи энергии; аппроксимация; магнитная индукция; прокатка; subsystem; mathematical models; electric steel; approximating function